Solely economic mitigation strategy suggests upward revision of nationally determined contributions - Yang, P; Mi, Z; Yao, Y-F; Cao, Y-F; Coffman, D; Liu, L-C (Elsevier, 2021)
The use of equity principles to review the nationally determined contributions (NDCs) is critical to facilitating more ambitious climate actions. However, disagreement over the equity principles persists. We instead treat emission reduction as a solely economic behavior motivated by avoiding future economic damage from climate change. Assuming no international cooperation, we provide a solely economic mitigation pathway to review national climate pledges until 2100. Using the value in 2030 to review the NDCs, we find that the NDCs of China, the USA, and the EU are 1.5, 1.4, and 0.9 respective GtCO2eq lower than their solely economic emission levels, whereas India commits 3.8 GtCO2eq more than its solely economic emission level. We also propose an equal-effort cooperation scenario toward 2°C where each country reduces emissions by 28% of their solely economic levels in 2030. Through exploration of the economic trade-offs, our results suggest that more ambitious NDCs are urgently needed.